MENYELARASKAN KEPENTINGAN POLITIK, BUDAYA, DAN BIROKRASI DALAM PERUMUSAN KEBIJAKAN PERTAHANAN - Aris Sarjito (Governance, 2024)
This research investigates the multifaceted challenges of defense policy formulation by addressing three primary questions: How does political polarization affect defense policy? In what ways do cultural factors influence national defense policies? What are the primary bureaucratic obstacles in defense policy formulation, and how can they be mitigated? Utilizing Political Polarization Theory, the study examines how ideological divides hinder consensus-building and lead to policy stagnation. Constructivist Theory of International Relations explores how cultural narratives, historical legacies, and national identity shape defense strategies. The Bureaucratic Politics Model analyzes internal power struggles and inter-agency rivalries that complicate policy formulation. Qualitative research methods using secondary data, including literature reviews, policy documents, and case studies, are employed to examine these dynamics. Findings indicate that political polarization leads to delayed and compromised defense policies, cultural factors significantly influence strategic priorities, and bureaucratic obstacles impede efficient policy implementation. The study concludes with recommendations for mitigating these obstacles through strategic reforms, enhanced inter-agency coordination, and the adoption of new technologies. This research provides comprehensive insights for policymakers to navigate the complexities of defense policy formulation.